Policy Implementation of PBB-P2 Collection in North Morowali Regency - Ndama, Jein Helvina; Alamsyah, M. Nur; Nuraisyah, Nuraisyah (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to analyze the implementation of Rural and Urban Land and Building Tax (PBB-P2) collection in North Morowali Regency as an effort to optimize local revenue. A qualitative descriptive approach was applied, with data collected through observations, in-depth interviews, and document analysis. The findings reveal that policy implementation remains suboptimal. Communication with taxpayers is limited, as information dissemination is only conducted through village officials without direct community involvement. While physical resources are generally adequate, human resource shortages—particularly tax bailiffs and auditors—hinder legal enforcement procedures. The disposition of tax officers, including assignment and incentives, is in accordance with applicable regulations and has been effectively managed. The bureaucratic structure reflects essential characteristics, including Standard Operating Procedures (SOPs) and inter-agency coordination. Internal constraints include limited staff capacity and low tax competence, while external challenges involve a lack of taxpayer awareness. On the other hand, supporting factors include strong leadership, adequate infrastructure, and regulatory reinforcement through Regional Regulation No. 9 of 2023. The study recommends strengthening public communication and enhancing human resource competence to improve the effectiveness of PBB-P2 collection.